PENGGUNAAN INSTAGRAM SEBAGAI STRATEGI DAKWAH USTADZAH OKI SETIANA DEWI DALAM MEMBENTUK AKHLAKUL KARIMAH FOLLOWERS - Kamila, Ayu Husnah; Muslikhah , Febri Palupi (Fakultas Ilmu Dakwah dan Komunikasi, 2023)
This study aims to determine the strategy of Ustadzah Oki Setiana Dewi da'wah on the Instagram account in increasing the morals of karimah followers. This approach uses descriptive qualitative research methods. This research involved informants from Ustadzah Oki Setiana Dewi's Instagram followers.The result of this research is that the da'wah strategy used by Ustadzah Oki Setiana Dewi on Instagram has succeeded in effectively shaping the character of karimah in his followers with inspiring, educational, and relatable content. A modern and creative approach through social media can be an effective tool in conveying religious messages. Ustadzah Oki Setiana Dewi applies strategies that blend with contemporary lifestyles, packaging da'wah information in a way that is relevant to her followers on Instagram. bond between religion and the social life of modern society. Positive interaction through Instagram also allows for a strong relationship between speakers and followers.